ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH - Umasangadji, Umaya (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
The aim of this research is to analyze the influence of local original income, general allocation funds and special allocation funds on the level of regional financial independence in districts/cities in North Maluku province. The objects of this research are all Regency in North Maluku province. There are 50 data in this research. Data was obtained from the BPK RI Office representing North Maluku Province. The data is in the form of an APBD Realization Report which also contains data on regional financial independence which details the types of regional financial independence, balancing funds, regional original income. The test tool used is multiple regression analysis. The results of this research show that: (1) Regional original income has a positive effect on regional financial independence, the greater that the regional original inxome the greater the regional financial independence (2) General allocation funds have a negative effect on regional financial independence,  the greater the general allocation funds distributed by the government to a region, the smaller the level of financial independence of that region (3) Special allocation funds have a negative effect on regional financial independence. the greater the special allocation funds received by the region, the lower the regional financial independence